The impact of increasing vs. decreasing harassing behaviours on perceptions of hypothetical instances of repeated sexual harassment. Issue 2 (4th May 2019) - Marks, Michael J.; An, Sieun
ABSTRACT: Sexual harassment is a traditionally underreported crime. One factor that might affect perceptions and willingness to report harassment is its occurrence over time: harassing behaviours that gradually increase or decrease in severity over time might impact its perception. In the present research, 177 female participants read a series of daily scenarios about increasing, decreasing, or steady harassment, and completed measures regarding their perceptions of and willingness to report it. Participants displayed increases and decreases in negative reactions as harassment increased and decreased, respectively, suggesting that each instance of sexual harassment is interpreted independently of earlier harassing behaviours, and that early, strongly harassing behaviours have little impact on how subsequent instances of harassment are perceived. This explanation is supported by the similar ratings in the midpoint (day 4) of the scenario series, regardless of whether harassment was increasing or decreasing.